2014
DOI: 10.1115/1.4026298
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Micro Electro-Discharge Machining Plasma Discharge in Deionized Water

Abstract: For successful commercial adaptation of the ß-EDM (micro electro-discharge machining) process, there is a need to increase the process efficiency by understanding the process mechanism. This paper presents a model of the plasma discharge phase of a single discharge ß-EDM event in deionized water. The plasma discharge is modeled using global model approach in which the plasma is assumed to be spatially uniform, and equations of mass and energy conservation are solved simultaneously along with the dynamics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 25 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…Due to complexities involving micro-EDM plasma, dielectric medium, melt-pool formation at both tool and workpiece electrodes, plasma collapse, and flushing of the dielectric etc., the heat flux, pressure, and radius of the plasma are obtained separately by simulating a micro-EDM model [9] and thereafter, the melt-pool formation due to a single discharge micro-EDM event is modeled based on the outputs of the plasma model. As shown in Fig.…”
Section: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to complexities involving micro-EDM plasma, dielectric medium, melt-pool formation at both tool and workpiece electrodes, plasma collapse, and flushing of the dielectric etc., the heat flux, pressure, and radius of the plasma are obtained separately by simulating a micro-EDM model [9] and thereafter, the melt-pool formation due to a single discharge micro-EDM event is modeled based on the outputs of the plasma model. As shown in Fig.…”
Section: Model Formulationmentioning
confidence: 99%
“…A brief discussion of the global micro-EDM plasma discharge model that provides the plasma heat flux, pressure and plasma radius inputs to the melt-pool model is given in Sec. 2 [9,13,14] is used, which assumes uniform spatial distributions of plasma characteristics and [9], which consists of three submodules, namely, plasma chemistry that solves the reaction kinetics involving ionization, dissociation, and recombination reactions; power balance that solves for the temperature of the plasma; and bubble dynamics module that gives the evolution of plasma geometry during the discharge. More details of the model are provided elsewhere [9].…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies mainly focus on spectroscopic measurements [6][7][8][9][10][11], simulation analysis of discharge plasma [12][13][14][15], and reverse deduction according to discharge pit morphology [16,17]. Kojima et al [11] studied the expansion process of and temperature distribution in plasma channels by using spectroscopic and high-speed video technology and reported that plasma channels can expand completely in just a few microseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Kapoor et al [6] and Ramkumar et al [6][7][8] investigated the temperature distribution and electron density in plasma channels by spectroscopic technology. Mujumdar et al [14] conducted a simulation to determine the composition, temperature of electrons and other ions, radius, and inner pressure of plasma channels; a model of a microdischarge channel in deionized water was developed after deriving assumptions and solving mass and energy conservation equations. Zhang et al [17] indirectly studied the expansion process of plasma channels by measuring the geometry of a discharge pit, including the recast area; they found that the radius of plasma channels changes over time.…”
Section: Introductionmentioning
confidence: 99%